Ga/Lu-labeled DOTA-TATE shows similar imaging and biodistribution in neuroendocrine tumor model - Fei Liu; Hua Zhu; Jiangyuan Yu; Xuedi Han; Qinghua Xie; Teli Liu; Chuanqin Xia; Nan Li; Zhi Yang (Tumor Biology)
Somatostatin receptors are overexpressed in neuroendocrine tumors, whose endogenous ligands are somatostatin. DOTA-TATE is an analogue of somatostatin, which shows high binding affinity to somatostatin receptors. We aim to evaluate the 68 Ga/ 177 Lu-labeling DOTA-TATE kit in neuroendocrine tumor model for molecular imaging and to try human–positron emission tomography/computed tomography imaging of 68 Ga-DOTA-TATE in neuroendocrine tumor patients. DOTA-TATE kits were formulated and radiolabeled with 68 Ga/ 177 Lu for 68 Ga/ 177 Lu-DOTA-TATE (M-DOTA-TATE). In vitro and in vivo stability of 177 Lu-DOTA-TATE were performed. Nude mice bearing human tumors were injected with 68 Ga-DOTA-TATE or 177 Lu-DOTA-TATE for micro–positron emission tomography and micro-single-photon emission computed tomography/computed tomography imaging separately, and clinical positron emission tomography/computed tomography images of 68 Ga-DOTA-TATE were obtained at 1 h post-intravenous injection from patients with neuroendocrine tumors. Micro–positron emission tomography and micro-single-photon emission computed tomography/computed tomography imaging of 68 Ga-DOTA-TATE and 177 Lu-DOTA-TATE both showed clear tumor uptake which could be blocked by excess DOTA-TATE. In addition, 68 Ga-DOTA-TATE–positron emission tomography/computed tomography imaging in neuroendocrine tumor patients could show primary and metastatic lesions. 68 Ga-DOTA-TATE and 177 Lu-DOTA-TATE could accumulate in tumors in animal models, paving the way for better clinical peptide receptor radionuclide therapy for neuroendocrine tumor patients in Asian population.